Artificial Intelligence and Sustainable Innovation: A Theoretical Review - Artha, Bhenu; Sari, Utami Tunjung; Bahri, Bahri; Hadi, Antonius Satria; Sari, Niken Permata; Asri, Cahya Purnama; Satriadhi, Bintoro (Institute Of Advanced Knowledge and Science, 2025)
Artificial intelligence (AI) has become universal across various sectors, permeating every aspect of our lives regardless of age or profession. In this era of AI, it's necessary to prioritize sustainable development and innovation in its application, while AI enables rapid completion of tasks alike human efficiency, it also raises concerns about increasing unemployment rates. A theoretical literature review is conducted in order to achieve the research's goals and objectives, and a conceptual framework for future study is offered. Authors conclude that artificial intelligence affects green product, artificial intelligence affects green energy, and artificial intelligence affects green farming.